Therapeutic Options for Patients Bleeding with Peptic Ulcers - ABR Thomson (Canadian Journal of Gastroenterology)
It is likely that the best outcome for the patient with an acute upper gastrointestinal bleed (GIB) includes early diagnosis: for a bleeding lesion with a high risk of rebleeding, in an older patient with systolic h.ypotension or in a person with multiple medical problems. Early therapeutic endoscopy with meticulous control of intragastric pH will Likely achieve the best outcome. The ideal pH criterion to stop bleeding or to prevent recurrence is unknown. An algorithm is presented to guide the clinical management of patients with GIB, and to focus on important questi.ons for future therapeutic studies.